(untitled) (Research, Society and Development, 2022)
Logistics companies have increasingly faced the challenges of last mile distribution, being expressed as a unit of measure, as the last logistics leg, that is, the final 1.6 km of a delivery. In this context, the problematic situation of this study falls: how is it possible to rethink the distribution of orders in order to optimize the external delivery process, considering the delivery person’s journey and the rationalization of organizational resources, for the ALFA company? In this context, the objective was to analyze the logistical process of delivery of orders (fractional loads) of the company ALFA, aiming to propose solutions for the rationalization of the last mile stage, in order to obtain gains for the company and for the customers. The research has an exploratory nature and the strategy used was the case study on the company ALFA. The main results obtained reside first in the methodological journey used, with a broad participation (internal and external), which made it possible to obtain a more systemic view of the process as a whole. A second point was to verify that not always the appearance of an initial problem can be totally correct and punctual solutions can help, but not necessarily solve problems that are systemic. Thus, more collaborative journeys or methodologies for problem identification can be interesting solutions. Third, the existence of support in the specialized literature for the solutions presented and the extension of the participation with internal and external actors, can generate more consistent views on organizational problems.